2013
DOI: 10.1016/j.placenta.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

A new method for measurement of placental elasticity: Acoustic radiation force impulse imaging

Abstract: ARFI imaging was observed to have no apparent histological damage to the placental tissue. Ex vivo placentas from the FGR group were significantly more firm. Moreover, Vs values and Z-scores of birthweight had a significant negative correlation. Additional investigations are needed about the utility of this method for the evaluation of placental function in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 15 publications
9
83
3
Order By: Relevance
“…Our results for the control group were in agreement with the results of Li et al (11). Our results are also compatible with a recent study on postpartum placentas, which reported higher elasticity values in the central region of the placenta of intrauterine growth-restricted fetuses and hypertensive pregnancies (12). Their elasticity values cannot be compared to ours due to their ex vivo study design.…”
Section: Discussionsupporting
confidence: 81%
“…Our results for the control group were in agreement with the results of Li et al (11). Our results are also compatible with a recent study on postpartum placentas, which reported higher elasticity values in the central region of the placenta of intrauterine growth-restricted fetuses and hypertensive pregnancies (12). Their elasticity values cannot be compared to ours due to their ex vivo study design.…”
Section: Discussionsupporting
confidence: 81%
“…Despite that the authors did not observe any histological damage to the placental tissue after ARFI examination and some researches confirm that temperature increase caused by pulse burst might still be within the safe limits determined by Food and Drug Administration [26][27][28], safety of ARFI or other similar techniques on pregnant should be carefully investigated.…”
Section: Placentamentioning
confidence: 87%
“…Results revealed a significant difference in shear wave velocity between FGR and normal group -higher in FGR group (1.94 ± 0.74 vs. ± 1.31 0.35, p < 0.05), and no significant difference between normal and PIH group. Moreover, authors noticed a correlation between increased velocity and decreased birth weight Z-score [26].…”
Section: Placentamentioning
confidence: 96%
“…It has been used for various diseases as well as in placenta pathology [13][14][15][16][17][18][19]. Acoustic radiation force impulse (ARFI) elastography is relatively a new method which uses a short acoustic push pulse in the target tissue, which causes a tissue displacement of approximately 1-20 um.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic radiation force impulse (ARFI) elastography is relatively a new method which uses a short acoustic push pulse in the target tissue, which causes a tissue displacement of approximately 1-20 um. Placental evaluation with ARFI elastosonography has been studied in hypertensive disorders and fetal growth restricted pregnancies and a stiffer placenta in both groups was reported [13]. To date, no study has been found which has evaluated the placental tissue stiffness in maternal red blood cell alloimmunization.…”
Section: Introductionmentioning
confidence: 99%